Novel Gemcitabine-Re(I) Bisquinolinyl Complex Combinations and Formulations With Liquid Crystalline Nanoparticles for Pancreatic Cancer Photodynamic Therapy - Liew, Hui Shan; Mai, Chun-Wai; Zulkefeli, Mohd; Madheswaran, Thiagarajan; Kiew, Lik Voon; Pua, Lesley Jia Wei; Hii, Ling Wei; Lim, Wei Meng; Low, May Lee (Frontiers in Pharmacology, 2022)
With less than 10% of 5-year survival rate, pancreatic ductal adenocarcinoma (PDAC) is known to be one of the most lethal types of cancer. Current literature supports that gemcitabine is the first-line treatment of PDAC. However, poor cellular penetration of gemcitabine along with the acquired and intrinsic chemoresistance of tumour against it often reduced its efficacy and hence necessitate the administration of high gemcitabine dose during chemotherapy. Photodynamic therapy (PDT), a more selective and minimally invasive treatment, may be used synergistically with gemcitabine to reduce the doses utilised and dose-related side effects. This study reports the synergistic use of Re(I) bisquinolinyl complex, a transition metal complex photosensitizer with gemcitabine against PDAC. Re(I) bisqinolinyl complex was found to act synergistically with gemcitabine against PDAC in vitro at various ratios. With the aim to enhance cellular uptake and therapeutic efficiency, the Re(I) bisquinolinyl complex and gemcitabine were encapsulated into liquid crystalline nanoparticles (LCNPs) system. The formulations were found to produce homogeneous drug-loaded LCNPs (average size: 159 to 173 nm, zeta potential +1.06 to -10 mV). Around 70% of gemcitabine and 90% of the Re(I) bisquinolinyl complex were found to be entrapped efficiently in the formulated LCNPs. The release rate of gemcitabine or/and the Re(I) bisquinolinyl complex loaded into LCNPs were evaluated in vitro and the hydrophilic gemcitabine was released at a faster rate than the lipophilic Re(I) complex. LCNPs loaded with gemcitabine and Re(I) bisquinolinyl complex in 1:1 ratio illustrated the best anti-cancer activity among the LCNPs formulations (IC50 of BxPC3: 0.15 μM; IC50 of SW1990: 0.76 μM) through apoptosis. The current findings suggest the potential use of transition metal-based photosensitzer as adjunctive agent for gemcitabine-based chemotherapy against PDAC and the importance of nano-formulation in such application.